Concepts and Images of Aging From the Perspective of Psychological Components in the Curriculum of the Primary School of the Iranian Educational System: Qualitative Content Analysis - Tayebeh Tajari; Mahindokht Javanneshan; Marziyeh Bayani (Sālmand, 2023)
Objectives The present study aims to analyze the content of primary school textbooks in the Iranian educational system based on the psychological components of the elderly and how these books have reproduced the psychological components of the elderly. Methods & Materials The research method was descriptive-content analysis. The statistical population of the study included primary school textbooks. The statistical sample of the desirable cases purposefully included the content of all primary school textbooks in 2020. Research components included self-acceptance, autonomy, personal growth, communication with others, environment mastery, and consciousness in life, as well as a content analysis unit. Results The results showed that primary school textbooks have addressed the problem of aging from a psychological perspective to some extent, but the texts and images have been at a low level in terms of content and quality of effect in primary school children, which is the period of their personality formation, and has indirectly introduced an elderly person disable and impressible. Therefore, these textbooks do not strongly reproduce the psychological characteristics of the elderly. Their presentation focuses more on the quality of communication with others and neglects other psychological components. Conclusion Iranian primary school curriculum requires a thorough review based on the psychological components of the elderly. Texts, activities, and elderly images are included in the textbook to pay more attention to the area of vitality and life expectancy. This practice creates an attitude and a sense of purposefulness in aging.